The thermal decomposition of irradiated silver permanganate - Sole, Michael John (Rhodes University, Faculty of Science, Department of Chemistry, 1959)
The thermal decomposition of silver permanganate, pre-irradiated in BEPO and in a â ¶Â°Câ‚€ Ïª 'hot spot' has been investigated in the temperature range 100 - 125Â°C. The results are similar to those for irradiated KMn0â‚„ and the mechanism proposed for the latter is again suggested. The activation energy for the migration of point defects over the induction period is 1.03 ev. The decompositions of unirradiated and irradiated crystals differ in that the latter undergo physical disintegration over the acceleratory period. X-ray studies immediately prior to disintegration show strain and fragmentation in the irradiated crystal. An explanation involving the annealing of point defects at dislocation is advanced to explain the changes produced in the p/t plots with increased dosage, and fixed decomposition temperature. Summary, p. 94.
Keywords: Decomposition (Chemistry); Irradiation; Permanganates; Silver compounds; Metals -- Thermal properties